Pandemic A/H1N1/2009 influenza virus in Swine, Cameroon, 2010 - (:unkn) unknown (My University, 2012)
Although swine origin A/H1N1/2009 influenza virus (hereafter "pH1N1″) has been detected in swine in 20 countries, there has been no published surveillance of the virus in African livestock. The objective of this study was to assess the circulation of influenza A viruses, including pH1N1 in swine in Cameroon, Central Africa. We collected 108 nasal swabs and 98 sera samples from domestic pigs randomly sampled at 11 herds in villages and farms in Cameroon. pH1N1 was isolated from two swine sampled in northern Cameroon in January 2010. Sera from 28% of these herds were positive for influenza A by competitive ELISA and 92.6% of these swine showed cross reactivity with pandemic A/H1N1/2009 influenza virus isolated from humans. These results provide the first evidence of this virus in the animal population in Africa. In light of the significant role of swine in the ecology of influenza viruses, our results call for greater monitoring and study in Central Africa.
Keywords: African Research